A Primary Role for the Tsix lncRNA in Maintaining Random X-Chromosome Inactivation - Srimonta Gayen; Emily Maclary; Emily Buttigieg; Michael Hinten; Sundeep Kalantry (Cell Reports, 2015)
Differentiating pluripotent epiblast cells in eutherians undergo random X-inactivation, which equalizes X-linked gene expression between the sexes by silencing one of the two X-chromosomes in females. Tsix RNA is believed to orchestrate the initiation of X-inactivation, influencing the choice of which X remains active by preventing expression of the antisense Xist RNA, which is required to silence the inactive-X. Here we profile X-chromosome activity in Tsix-mutant (XΔTsix) mouse embryonic epiblasts, epiblast stem cells, and embryonic stem cells. Unexpectedly, we find that Xist is stably repressed on the XΔTsix in both sexes in undifferentiated epiblast cells in vivo and in vitro, resulting in stochastic X-inactivation in females despite Tsix-heterozygosity. Tsix is instead required to silence Xist on the active-X as epiblast cells differentiate in both males and females. Thus, Tsix is not required at the onset of random X-inactivation; instead, it protects the active-X from ectopic silencing once X-inactivation has commenced.